Effects of Viscous Dissipation on Slip Velocity Boundary Layer Flow and Mixed Convection Heat Transfer - T. N. Vasanthakumari (International Journal of Mathematics And its Applications, 2024)
In the present study, we investigate the slip velocity and viscous dissipation effects on the boundary layer flow and mixed convective heat transfer over a stationary and rigid surface. The mainstream flow is considered to be varying linearly from the leading boundary layer. The governing boundary layer equations are reduced to a set of ordinary differential equations, using appropriate similarity transformation, which are then solved numerically using Keller-box method. The various results such as velocity and temperature profiles and wall shear stress and temperature gradients are obtained and presented. Our results show that both slip velocity and Eckert number are to influence the boundary layer thickness, velocity and temperature profiles. Particularly, the slip velocity effects are to flatten the boundary layer. The various other physical mechanisms behind these effects are discussed in detail.